2002
DOI: 10.1177/026988110201600312
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor mechanism(s) and morphine tolerance in mice

Abstract: Based on our previous demonstration of the involvement of dopamine-2 (D2) dopamine receptors in morphine antinociception, we examined the role of D2 dopamine receptors in the expression and development of tolerance to morphine antinociception in mice. Tolerance to morphine antinociception was assessed by the tail-flick response after the administration of morphine (50 mg/kg) once daily for 3 days. The D2 dopamine receptor agonist, quinpirole (0.01, 0.02 and 0.03 mg/kg), but not the D2 dopamine receptor antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Others recommended that both D2DR agonist quinpirole (i.p. )20 and D2DR antagonist sulpiride (i.p. )20, eticloride (i.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others recommended that both D2DR agonist quinpirole (i.p. )20 and D2DR antagonist sulpiride (i.p. )20, eticloride (i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of D2DR by quinpirole in hypothalamic A11 cell group17, ventrolateral orbital cortex (VLO)18 and dorsal hippocampus (CA1)19 of rats exerts antinociceptive effect. Intraperitoneal injection of quinpirole enhances the antinociceptive effect of morphine20. However, Michael A.…”
mentioning
confidence: 99%
“…Dopamine receptor agonists as well as antagonists have been shown to modulate the analgesic effects of morphine in animal models (Zarrindast et al 1999(Zarrindast et al , 2002. Metoclopramide is a D2 dopamine receptor antagonist, and additionally activates the serotonin 5HT 4 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…These effects of morphine that are named state-dependent learning have been demonstrated previously [3,4,29,30] . Moreover, it has been shown that repeated administration of morphine may induce tolerance to its own response [31] . However, repeated administration of morphine followed by a period of drugfree treatment might induce sensitization [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%